Evaluasi Implementasi Kebijakan Sumber Daya Manusia di Pemerintah Kabupaten Tanggamus - Fatqul Hajar Aswad (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2022)
This research done to know how implementation process policy of recruitment, selection and location of public servant of civil candidate from reguler at Tanggamus Regency with standard of criterion which have been formulated.This research represent research of evaluation by using model evaluate as developed by Malcolm Pravus. Subyek Responder is area secretary head Tanggamus Regency, Lead BKD and His Subordinate which become acceptance committee public servant of civil candidate from reguler. Step in this research consist of 5 phase that is compilation of desain, program installation, implementation process, Product and of cost implementation. Data collecting use observation technique, documentation study and interview. collected data analysis use model analyse interaktif of Miles and Huberman. Result of this research indicate that process acceptance of public servant of civil candidate from reguler at Tanggamus Regency have as according to regulation of minister of PAN-RB Number 197 Year 2012, Regulation of government Numbers 98 Year 2000 and Regulation of government number 11 year 2002 staying in moderating category tend to highly. All Step in this evaluation have been done according to following guidance / existing regulation effectively and efficient so that program policy of acceptance of public servant of civil can to be continued with repair a period of to come. Result of this research also strengthen theory of efektivitation implementation policy of public. Recommend some aspect which need to be corrected that is personnel data base , the importance of team evaluate and financial reporting of policy implementation base on internet.